2018
DOI: 10.1080/03088839.2018.1505054
|View full text |Cite
|
Sign up to set email alerts
|

The impact of dry port operations on container seaports competitiveness

Abstract: The concepts of intermodal logistics and distribution networks have made integration of the inland freight distribution system essential for an efficient container seaport system. Inland components, such as dry ports, which exist within the seaport system, have become important in shaping the performance and competitive strategies of container seaports. Owing to the importance of interdependence between dry ports and container seaports, this paper aims to investigate the impact of dry port operations on contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 41 publications
0
44
0
Order By: Relevance
“…Therefore, this paper has proposed the implementation of dry ports to reduce the negative effects of larger vessels on the Malaysian seaport system. Initially, research by Jeevan et al (2018b) indicated several implications of dry ports in the container seaport system due to general changes in maritime logistics, including enhancing seaport performance, increasing seaport service variations, reducing seaport-hinterland proximity, and increasing seaport trade volume and capacity (see Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this paper has proposed the implementation of dry ports to reduce the negative effects of larger vessels on the Malaysian seaport system. Initially, research by Jeevan et al (2018b) indicated several implications of dry ports in the container seaport system due to general changes in maritime logistics, including enhancing seaport performance, increasing seaport service variations, reducing seaport-hinterland proximity, and increasing seaport trade volume and capacity (see Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…Jeevan et al [10] investigated whether dry port operations have an impact on the competitiveness of ports, especially container ports. They conducted empirical research with object observations that were the main stakeholders of dry ports in Malaysia through 120 online surveys.…”
Section: "Relative Literature" On the Certain Topicmentioning
confidence: 99%
“…Measuring port competitiveness has also changed along with changes in their dynamic and complex business environment. Jeevan et al [10] focuses on inland components (such as dry ports) that exist in port systems, which are one of the important components to improve container port performance, in particular. Because of the importance of dry port and container port relationships, their research divided the main components of competitiveness and land supporting components for dry ports.…”
Section: The Impact Of the "Sea Toll" Program On Seaport Resilience Amentioning
confidence: 99%
See 2 more Smart Citations